Os discursos instrucional e regulador em programas de ciências: estudo comparativo de duas reformas - Isabel P. Neves; Ana Maria Morais; Ana Medeiros; Dulce Peneda (Universidade do Minho, 2000)
The study analyses the Natural Science syllabuses of the 5th/6th and 7th years of schooling to investigate the extent to which the present Portuguese reform (1991) for the elementary school introduces changes in the discourses and competences it values. The analysis used the conceptual framework of Bernstein´s theory. The results show changes in the present reform which suggest in general an increasing valuing of the regulative dimension of learning. The results also show a greater diversity and specification of the complex cognitive and socio-affective competences. The study also points out to a recontextualizing within the syllabuses, when passing from the curricular level to the disciplinary level, in the direction of bluring the changes observed.